Value Stream Mapping for Process Improvements in A Bakeware Company - Garzon, Juan Pablo (2006)
Value stream mapping (VSM) has been underway on a broad scale for the last decade in big companies such Toyota and Boeing; it is a tool that analyzes and identifies the waste in material flow and information flow. This project considers the implementation of value stream mapping on two products that are made by a bakery system company and focuses on product family, current map and the future map as well as the improvements made. The aim is to identify waste and then translate the waste opportunities to improve company performance. Researches, Tapping and Womark have developed two frameworks in value stream mappping which can be used in any type of business. The main issues of these are highlighted in the project. With regard to the current map, it is used to find opportunities to implement other lean tools. It is concluded that value stream mapping is the first tool that any company should use to implement lean systems. Also, the implementation of one piece flow in the shop floor could reduce the lead time, cycle time and level of inventories. This may be of interest to companies that work in a make to order environment and other companies that would like to become lean. Also, companies that start the lean journey can use this as a guideline to draw the current state map and find the future state.